Transthyretin cardiac amyloidosis: an under-diagnosed cause of heart failure - Gabriela Molina O; Daniel Judge; Wayne Campbell; Harjit Chahal; Marc Mugmon (Greater Baltimore Medical Center, 2014)
Introduction: Cardiac amyloidosis is the most common cause of infiltrative cardiomyopathy and is associated with a poor prognosis. Transthyretin cardiac amyloidosis, particularly the type caused by the mutation that replaces the amino acid valine with the amino acid isoleucine at position 122 (Val122Ile), is most common among African- Americans above 65 years of age. Evidence suggests that this mutation is an important, though under-diagnosed, cause of heart failure in this population. Case presentation: A 74-year-old African American male with a diagnosis of non-ischemic cardiomyopathy for several years, presented with gradually worsening dyspnea on exertion and lower extremity edema. There is no known cardiac disease in his family. An echocardiogram was done showing a decrease in ejection fraction to 30% from 45% in the span of a year. An endomyocardial biopsy analysis identified transthyretin amyloid with the Val122Ile mutation, confirming the diagnosis of familial transthyretin cardiomyopathy. Discussion: Systemic amyloidosis is a group of diseases caused by the deposition of an abnormally folded, insoluble protein that can accumulate in multiple organs causing progressive and irreversible dysfunction.The mutations that most commonly induce variant transthyretin cardiac amyloidosis are Val122Ile, Val30Met and Thr60Ala. The Val122Ile mutation has been found to be present in 3-4% of the African American/Caribbean population. Conclusions: Familial amyloid cardiomyopathy is an uncommonly recognized cause of heart failure in the population, and patients may wait several years before accurate diagnosis, risking additional significant irreversible deterioration. Patients that meet the high-risk profile criteria - male gender, age 65 years and older, heart failure symptoms, symmetric left ventricular (LV) hypertrophy, and moderately depressed LV function - should likely undergo additional testing for cardiac amyloidosis.